Kajian Kebutuhan Bahan Bakar Gas Pada Insinerator Limbah Medis Dual Chamber Dengan Variasi Laju Volume Injeksi Oksigen Dan Penambahan Injeksi Air - Sadhu Waskita, Nyoman; Suprapta Winaya, I Nyoman; Arya Darma, I Wayan; Angga Yuda Pratama, I Putu (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstractt This study conducted the process of medical waste incineration in a dual-chamber medical waste incinerator with oxygen injection and the addition of water injection in the second combustion chamber. The study varied the oxygen flow rate at volumes of 4, 6, 8, and 10 L/minute, using medical waste weighing 1 kg. The aim of this research was to determine the consumption rate of LPG gas fuel during combustion. The incineration process was carried out with a temperature of 800°C in the first combustion chamber and 1000°C in the second combustion chamber. The results obtained indicate that as the flow rate of oxygen volume increases, the consumption rate of LPG gas fuel required decreases. The optimal consumption rate of fuel gas was found at a variation of oxygen volume flow rate of 8 L/minute, which amounted to 6.5 kg/hour. Keywords: Dual Chamber Fixed Grate Incinerator, Oxy-fuel, Water Injection